Mobile Learning “Asmeralda” for Teaching Static Fluid at Senior High Schools - Iman Alkautsar; Mita Anggaryani (Universitas Lambung Mangkurat, 2022)
This study applied Research and Development (R&D) method for developing a mobile learning media for teaching static fluid material, namely